Seni motif tatu tradisional masyarakat Iban dan Kayan-Kenyah di Sarawak - Fujica, Anak Anggo (Universiti Malaysia Sarawak (UNIMAS), 2016)
This research aim to investigate the concept of Than and Kayan-Kenyah traditional tattoo art, examine the process of making a tattoo between traditional and modern methods and to observe the adaptation process between the Than and Kayan-Kenyah traditional tattoo art. This research focuses on Than and Kayan-Kenyah traditional tattoo motifs in Sarawak, Malaysia. As for the Than community, the body tattoo is known as Kelingai or Pantang. While for the Orang Ulu, it is known as Tedak (Kayan) and Betiek (Kenyah). The tattoos on their bodies are not just merely for decoration but it has a very deep inner meaning which symbolizes one's social status in the community. There are similarities and differences between the traditional tattoo motifs for the Than and Kayan-Kenyah community. For example, the similarities are found in flora and fauna motifs. The difference is found where they placed the tattoo on their bodies. If Bungai Terong, Kala (Scorpion) and the Engkatak motifs are used by the Than community, the dog motif (Udo Asu) and fruits (Uma Pliau) are used by the Kayan-Kenyah community. In the era of modernization, the art of traditional tattoo motifs is diminishing due to changes of lifestyle, artistic value and belief Among the younger generation, the contemporary tattoo is used for self identity and expression.